Strokes associated with left ventricular assist devices. Issue 9 (7th August 2018) - Kislitsina, Olga N.; Anderson, Allen S.; Rich, Jonathan D.; Vorovich, Esther E.; Pham, Duc T.; Cox, James L.; McCarthy, Patrick M.; Yancy, Clyde W.
Abstract: Ventricular assist devices (VADs) have improved dramatically over the past several decades but stroke remains a problem. There are multiple etiologies of both ischemic and hemorrhagic strokes associated with VADs. While this problem is yet to be solved, there are continuing efforts at improving the design of VADs to decrease the incidence of stroke and to improve long‐term survival in patients requiring mechanical circulatory assistance. The purpose is to review the incidence and underlying causes of stroke in VAD patients.